The Complexity And Compatibility Of ICT Integration In The Teaching And Learning Of Agriculture In Swaziland - Dludlu , Mzomba Nelson; Mndzebele, Nomsa (Advances in Social Sciences Research Journal, 2020)
In Swaziland, ICT integration in teaching and learning is at the infancy stage. Learning opportunities provided by the increasing use of technology in classrooms are not being harnessed in secondary schools. The purpose of the study was to describe ICT integration in the teaching and learning of Agriculture in relation to complexity and the compatibility of the ICT tools in Swaziland. Specific objectives were (1) to describe the complexity of ICT tools as perceived by the teachers and (2) to further describe the compatibility of ICT tools in relation to the teachers’ experiences. A descriptive correlational design employing a mixed method approach was used to conduct the study. Data was collected using a Semi-structured interview guide and a survey questionnaire. The population for the study was (N=325) involving all secondary school Agriculture Teachers (N= 312) and key informants who were Agricultural Education Administrators (n=13). The Unified Theory of Acceptance and Use of Technology (UTAUT) guided the study. Descriptive statistics were used to analyse data. With regard to complexity findings revealed that (1) computers make teaching of complex concepts easy, (2) computer use fits well in my curriculum goals, and that (3) learning to use ICT in teaching is a challenge. In overall findings indicated that the ICT tools were less complex to use by the Agriculture Teachers while teaching. The study further revealed that complexities of ICT use by Agriculture teachers were brought about by the age of teachers and the frequent changing of technologies. In relation to compatibility of ICT usage findings revealed that Agriculture Teachers agreed that (1) ICT is quick in meeting information needs, (2) Working with computers make them feel comfortable, (3) ICT use in teaching was very convenient, (4) Agriculture requires more ICT assistance, (5) computers brought positive changes in the schools, and that (6) computer use suits the learners needs. The study further indicated that Agriculture teachers perceived that ICT devices were (7) compatible with existing practices, (8) ICT philosophy was compatible with the subject content, and that (9) ICT integration allows well demonstration of real situations. It is recommended that a policy articulating the need and usage of ICT integration to support teaching and learning be enacted, thus, compelling Internet service providers to extend their bandwidth of Internet to all schools. It is further recommended, that ICT integration pedagogical skills be part of all pre-service and in-service teacher preparatory programmes.